Proyecto de conservación y adecuación de la casa habitación en Santiago Tapia #31 Morelia, Michoacán - Merlos Fernández, Sandra Ivonne (Universidad Michoacana de San Nicolas de Hidalgo, 2013)
In this work, is exposed the complex issues presented by the traditional house of the Historic Center of Morelia, linked to the close relationship between society-city, which has influenced its transformation and conservation. The house as a study object represents a significant element of cultural identity and spatial part of the physical signs that constitute the urban memory of the historic city. Housing shortage represents for human a build space that gives privacy, protection, and adapts to his daily life. What gives its symbolic meaning and utility, linked with a social value it can be individual or collective. This built heritage over time has been adapting its build spaces to new uses, generated by new life forms of contemporary societies, influencing the process of depopulation and transformation of housing in historic centers. On the other hand based on the idea of conservation of built heritage with a social vision, considering a well- used collectively inherited, in this sense does not mean doing only asset reference to the historical and artistic, but to everything that is built and may be subject to reuse. From this view is established by conservation project and adequacy of dwelling situated in Santiago Tapia Street No.31, which is located in the Historic Center of Morelia, considered within the protected heritage list decree published in the Official Journal of the Federation of December 19, 1990. The purpose of the intervention project is to encourage residential uses are kept in the Historic center. In the intervention project establish spaces has been adapted to accomplish two houses respecting the spatial organization, acting on the criteria for restoration based on respect for the historicity and reversibility in the proposed intervention. The propose allowing as a self-sustaining project, which will generate an economic benefit to the owner.

En el presente trabajo se aborda la compleja problemática que presenta la vivienda tradicional del Centro Histórico de Morelia, vinculada a la estrecha relación que existe entre sociedad- ciudad, lo que ha influido en su transformación y conservación. La casa habitación como objeto de estudio representa un elemento significativo, de identidad cultural y espacial que forman parte de las señales físicas que conforman la memoria urbana de la ciudad histórica. La vivienda representa para el ser humano un espacio que le da privacidad, protección, y se adapta a su cotidianidad. Lo que le da su significado simbólico y utilitario, vinculado con su valor social de carácter individual o colectivo. Este patrimonio edificado con el paso del tiempo ha venido adecuando sus espacios a los nuevos usos, generados por las formas de vida de las sociedades contemporáneas, influyendo en los proceso de despoblamiento y transformación de la vivienda en los centros históricos. Por otro lado partiendo de la idea de la conservación del patrimonio edificado con una visión social, considerando un bien heredado objeto de utilización colectiva, en este sentido lo patrimonial no significa hacer solo referencia a lo histórico-artístico, sino a todo aquello que está construido y puede ser objeto de reutilización. Desde esta visión se plantea el proyecto de conservación y adecuación de la vivienda ubicada en la calle Santiago Tapia No.31, ubicada en el Centro Histórico de Morelia, considerada dentro de la lista del patrimonio protegido por decreto publicado en el Diario Oficial de la Federación del 19 de diciembre de 1990. La finalidad del proyecto de intervención es promover que se conserven los usos habitacionales en el centro histórico.
Facultad de Arquitectura. Especialidad en Restauración de Sitios y Monumentos
Keywords: info:eu-repo/classification/cti/4; FA-E-2013-1429; Inmueble; Centro histórico; Mantenimiento; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3189